Poverty Reduction in Coastal Community Area through Marine Tourism Development: A Case Study of Pemuteran Village - Erapartiwi, Kadek Oka (Institut Pariwisata dan Bisnis Internasional, 2019)
This study investigates marine tourism’s contribution to poverty reduction amongst communities living in the coastal area. The study mainly employed a qualitative research design and data were collected through a mixed method approach involving interviews with a wide range of community members directly involved with tourism and observation. Some data was also gathered from secondary sources. The findings indicate that marine tourism brings benefits and played an important role in improving the living conditions of the poor in Pemuteran village. The study also identified several problems existing within the coastal community. Some of these barriers included lack of having adequate English from the villagers who are mostly traditional fishermen and lack of broad-based management structures. The study concludes that marine tourism has the potential to contribute to poverty reduction in Pemuteran village. This can only happen if there is a unity of purpose and renewed cooperation amongst all tourism stakeholders, transparency and accountability in financial matters.